2019
DOI: 10.7224/1537-2073.2017-089
|View full text |Cite
|
Sign up to set email alerts
|

Short Report: Adherence to Neuropsychological Recommendations in Patients with Multiple Sclerosis

Abstract: Background: Adherence to nonmedication recommendations is typically low, as seen in various health populations. Because literature on adherence to treatment recommendations made after neuropsychological testing in multiple sclerosis (MS) is lacking, this study evaluated adherence and reasons for nonadherence. Relationships between adherence to recommendations and various other factors in patients with MS were also evaluated. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Given that research has identified low adherence rates to neuropsychological testing recommendations in multiple sclerosis (38%), it may be preferable to provide additive follow-up care (in-person feedback and case management) where possible, to improve compliance and increase utility for such an intervention. 14,31,35,36…”
Section: Discussionmentioning
confidence: 99%
“…Given that research has identified low adherence rates to neuropsychological testing recommendations in multiple sclerosis (38%), it may be preferable to provide additive follow-up care (in-person feedback and case management) where possible, to improve compliance and increase utility for such an intervention. 14,31,35,36…”
Section: Discussionmentioning
confidence: 99%
“… Ruppert & Attix, 2014 Book chapter Brief summary of purposes and recommended practices for providing feedback on cognitive test results to patients and caregivers P: patients with a cognitive impairment N/A Recommendations given for in-person feedback, such as clear communication, querying understanding throughout session, allowing patients/family to take notes, and provide written materials. Stimmel et al, 2019 Research paper Explore rates of adherence to neuropsychological recommendations, reasons for nonadherence, and the effect of oral (phone call) and written feedback over written feedback alone D: quantitative, descriptive P: 55 patients with MS S: MS center (medical center) M: semi-structured interview, retrospective record review O: adherence to treatment recommendations Self-reported adherence to recommendations was 38%, but this varied per recommendation type (high adherence for pharmacological management and lower for psychotherapy or psychiatry referral/cognitive rehabilitation). Reasons for nonadherence were needing more information and wanting to speak with physician.…”
Section: Resultsmentioning
confidence: 99%
“…Most research papers used in-person feedback (Arffa & Knapp, 2008 ; Cheung et al, 2014 ; Connery et al, 2016 ; Fallows & Hilsabeck, 2013 ; Farmer & Brazeal, 1998 ; Foran et al, 2016 ; Holst et al, 2009 ; Kirkwood et al, 2016 , 2017 ; Lanca et al, 2019 ; Lopez et al, 2008 ; Malla et al, 1997 ; Meth et al, 2016 ; Rosado et al, 2018 ; Tharinger & Pilgrim, 2012 ; Westervelt et al, 2007 ; Gruters et al, 2020 ; Martin & Schroeder, 2020 ), and most of the other publications recommended in-person feedback (Allen et al, 1986 ; Carone et al, 2010 ; Carone et al, 2013 ; Carone, 2017 ; Crosson, 2000 ; Gass & Brown, 1992 ; Gorske, 2007 ; Gorske & Smith, 2009 ; Green, 2000 ; Griffin & Christie, 2008 ; Postal & Armstrong, 2013 ; Ruppert & Attix, 2014 ). A minority gave feedback via phone (Stimmel et al, 2019 ), via telemedicine (Clement et al, 2001 ; Turner et al, 2012 ) or via a written report (Evans et al, 2019 ). Usually, feedback was given by the neuropsychologist a few weeks after the assessment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple sclerosis (MS) is a chronic, inflammatory, demyelinating condition that can present with diverse patterns of physical, cognitive, and psychiatric symptoms [1][2][3][4]. In addition to expert care provided by neurologists who may provide clinical monitoring and pharmacological intervention (e.g., dimethyl fumarate, interferons, monoclonal antibodies) [5,6], clinical neuropsychologists are often called upon to assess such patients and provide targeted treatment recommendations for them from a neurocognitive and psychological perspective [7,8]. Several attempts to standardize the clinical neuropsychological assessment of patients with MS (pwMS) have been made.…”
Section: Introductionmentioning
confidence: 99%